Ensuring strategic sensitivity of knowledge–intensive industrial enterprises - M. V. Dulyasova; D. V. Morozov; A. V. Budantsev (Путеводитель предпринимателя)
The main trends in the development of high–tech industrial enterprises in the Russian Federation are considered. The structure of the system of interaction of a science– intensive industrial enterprise with the state and small business is proposed, which ensures the strategic stability of a certain «basic part» of their business processes and at the same time, which allows, based on the use of the advantages of small business, to ensure high sensitivity of its activities in the implementation of strategic and operational plans.